(untitled) (Plant Tissue Culture and Biotechnology, 2011)
High frequency direct shoot proliferation was induced from the shoot tip explants derived from the in vitro grown seedlings of a critically endangered and horticulturally important ground orchid Phaius tancarvilleae (L’Her) Blume. Shoot tip explants cultured on solidified MS with alone or combination of various concentrations of NAA and BAP produced shoots and multiple shoots. The maximum number of healthy shoots was observed on MS with BAP (1.0 mg/l) with an average of 13.3 shoots per culture in 20 weeks; where shoot multiplication was initiated after 4 weeks of culture. Regenerated shoots rooted on MS with various concentrations of NAA, IAA, IBA. MS with NAA (0.5 mg/l) was the most appropriate condition for rooting. The well developed in vitro rooted plantlets were hardened successfully in the potting mixture containing cocopeat and sphagnum moss in the ratio of 2 : 1. Key words: Mass propagation, Phaius tancarvilleae, shoot multiplication D. O. I. 10.3329/ptcb.v21i2.10241 Plant Tissue Cult. & Biotech. 21(2): 181-188, 2011 (December)